Integrated assessment of international climate mitigation commitments outside the UNFCCC. (January 2018) - Roelfsema, Mark; Harmsen, Mathijs; Olivier, Jos J.G.; Hof, Andries F.; van Vuuren, Detlef P.
Highlights: Climate action outside the UNFCCC can accelerate implementation and add additional reductions to NDCs. These reductions are projected to be of similar magnitude as NDCs. But overlap between these initiatives and NDCs is assumed to be large, around 70–80%. This is insufficient to close the gap between NDCs and the 2 °C limit. Non-state actors data needs to be more publicly available and monitoring and reporting improved. Abstract: In the Paris Agreement under the United Nations Framework Convention on Climate Change (UNFCCC), for the first time, non-state actors were addressed in the international negotiations and were explicitly invited to act on climate change. Indeed, there are many transnational emission reduction initiatives (TERIs) outside the UNFCCC, driven by non-state actors or national governments, which aim at reducing greenhouse gas (GHG) emissions. Using an Integrated Assessment Model (IAM), this study assessed the potential impact of a selection of large TERIs that existed before the Paris Agreement on global greenhouse gas emissions. TERIs could lead to significant emission reductions: the eleven selected initiatives included in the analysis here could – if fully implemented – deliver annual GHG emission reductions of 2.5 GtCO2 eq by 2020 and of 5.0 GtCO2 eq by 2030 from a no-policy-baseline emission level of 53.7 GtCO2 and 61.1 GtCO2 eq, respectively. Although these reductions are of similar magnitude as those pledged by countries under the umbrella of the UNFCCC, these reductions may significantly overlap with those of pledges and Nationally Determined Contributions. The maximum estimate of overlap is around 70% by 2020 and 80% by 2030. This means that the combined impact on global GHG emissions of TERIs and NDCs, assuming a maximum overlap, would lead to emission levels between 53 and 55 GtCO2 eq by 2030, compared to a level of 54 to 56 GtCO2 eq resulting from NDCs alone.